Self‐Assembly of Chiro‐Optical Materials from Nonchiral Oligothiophene‐Porphyrin Derivatives and Random Coil Synthetic Peptides. Issue 1 (29th September 2022) - Arja, Katriann; Selegård, Robert; Paloncýová, Markéta; Linares, Mathieu; Lindgren, Mikael; Norman, Patrick; Aili, Daniel; Nilsson, K. Peter R.
Abstract: Biomimetic chiral optoelectronic materials can be utilized in electronic devices, biosensors and artificial enzymes. Herein, this work reports the chiro‐optical properties and architectural arrangement of optoelectronic materials generated from self‐assembly of initially nonchiral oligothiophene−porphyrin derivatives and random coil synthetic peptides. The photo‐physical‐ and structural properties of the materials were assessed by absorption‐, fluorescence‐ and circular dichroism spectroscopy, as well as dynamic light scattering, scanning electron microscopy and theoretical calculations. The materials display a three‐dimensional ordered helical structure and optical activity that are observed due to an induced chirality of the optoelectronic element upon interaction with the peptide. Both these properties are influenced by the chemical composition of the oligothiophene−porphyrin derivative, as well as the peptide sequence. We foresee that our findings will aid in developing self‐assembled optoelectronic materials with dynamic architectonical accuracies, as well as offer the possibility to generate the next generation of materials for a variety of bioelectronic applications. Abstract : Chiral construction : By mixing anionic oligothiophene−porphyrin derivatives and cationic synthetic peptides, self‐assembled optoelectronic materials with distinct photo‐physical properties and specific architectonical arrangement can be afforded. The chemical composition of the oligothiophene−porphyrin derivative, as well as the sequence of the peptide, had large effects on the induced circular dichroism and the structure of the self‐assembled supramolecular structures.